The role of parents in providing sexuality education to their children - Binti Abdullah, Nur Azira Fideyah; Muda, Siti Mariam; Mohd Zain, Norhasmah; Abdul Hamid, Siti Hazariah (UI Scholars Hub, 2020)
Background: Parents have an important role in delivering sexuality education to their children. However, Asian parents are reluctant to discuss sexual matters with their children owing to the sensitivity of the topic and their lack of sexual health knowledge. This study aimed to examine Malaysian parents’ knowledge, attitudes, and practices in providing sexuality education to their children. Methods: A self-administered questionnaire was used to conduct this cross-sectional study featuring 200 Malaysian parents. Descriptive and univariate analyses were performed using Statistical Package for Social Study (SPSS) version 23.0. Results: Among the majority (79.5%) of the parents having good knowledge, 82% agreed that sexuality information helps their children recognize and avoid sexual abuse. Most (91%) of them perceived that they have good practices in providing sexuality education to their children. There is no association between the parents’ gender and their knowledge of sexuality education. However, there are no links between age groups, educational level, and the parents’ knowledge of sexuality education. Conclusion: Malaysian parents believe that sexuality education should be provided by the parents to their children at an early age. Hence, a comprehensive sexuality education program for parents consisting of sufficient information, motivation, and strategies, is needed to develop children’s sexual literacy.